PERAN PERGURUAN TINGGI DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN - Khoirurrijal Khoirurrijal (Ri'ayah: Jurnal Sosial dan Keagamaan, 2016)
ASEAN Economic Society forces the workers to compete for employment opportunities in ASEAN countries, especially local workers from South East Asia. The workers who have high job competition absolutely receive more benefit than others. Improving human resources is needed to face this situation, especially for University graduates, to create international graduates who have professional skills, language skills, and cross-cultural skills. To fulfill the international standard, the University must increase their lecturer quality, curriculum, and facilities. Universities are also to develop good cooperation ability with others institution and development student’s activity unit which is expected to create educated and skilled human resources. Indonesia will become the big country and capable of being “Man of the Match” or it could even be worse because of the its competition as the of joining MEA.